2011
DOI: 10.1007/s13258-011-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic diversity of wild and hachery populations of Korean threadsail filefish Stephanolepis cirrhifer using cross-species microsatellite markers

Abstract: The threadsail filefish Stephanolepis cirrhifer is a highly commercial fisheries resource in Korea that suffers intensive anthropogenic pressure across much of its range. For basic information about its current genetic status in relation to stock enhancement, the level and distribution of genetic variation between a wild and a hatchery-bred population were investigated using 10 microsatellite markers developed for Thamnaconus modestus. High levels of polymorphism were observed between the two populations. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
3
2
Order By: Relevance
“…A similar phenomenon was also observed in a previous microsatellite analysis (An et al, 2011a). It is possible that null or non-amplifying alleles could account for the heterozygote deficiencies in the data.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar phenomenon was also observed in a previous microsatellite analysis (An et al, 2011a). It is possible that null or non-amplifying alleles could account for the heterozygote deficiencies in the data.…”
Section: Discussionsupporting
confidence: 87%
“…Although allelic diversity in terms of the number of alleles per locus has been shown to be variable depending on the sample size, the sample size of offspring in this study was larger than that of the parent population. We found that genetic diversity was similar in S. inermis, but the number of alleles per locus was relatively higher than that reported by An et al (2011a). Because allele number is positively correlated with sample size (Liu et al, 2009), the number of alleles observed in this study was probably due to the relatively large sample size.…”
Section: Discussioncontrasting
confidence: 44%
“…Conservation of genetic diversity is important for the long-term objective for marine species (Falk & Holsinger, 1991). Although many studies have found significant reductions in genetic diversity of offspring compared with broodstock, no significant difference was detected between broodstock I and offspring in this study (Reily et al , 1999; An et al , 2011a, b). High levels of genetic diversity in wild populations of fish can be related to large effective population size, environmental heterogeneity, life history traits and genetic divergence (Nei, 1987; Xiao et al , 2016).…”
Section: Discussioncontrasting
confidence: 73%
“…However, nonrandom mating, and/or artificial selection forces in play during seed production, may account for any deviation from HWE in broodstock. In offspring, heterozygote deficiency is commonly caused by a limited number of founders, inbreeding, or both (Kohlmann et al 2005;An et al 2011b). Such a deficit may also be attributable to inappropriate domestication of hatchery populations.…”
Section: Discussionmentioning
confidence: 99%